Explaining the Meaning of ‘Grey Zones’ in Public International Law Based on the Example of the Conflict in Ukraine (Contemporary Central & East European Law, 2020)
The aim of this paper is to analyse four domains of ‘grey zones’ in public international law exploited by Russia’s activities during the conflict in Ukraine – acknowledgement of Russia’s involvement in the conflict; the use of force against Ukraine; the application of the right to self-determination; and passportisation carried out in Donbass. As this paper will demonstrate, legal assessment of the Russian actions is not impossible, although also not straightforward. It is only the resilience of public international law that may allow for the declaration of Russian actions as illegal, and the bringing of Russia to justice. The paper is divided into five parts: the first part defines the term ‘grey zone’ with regard to international law. The four sections following this are focused on the analysis of particular Russian actions as examples of conduct undertaken in the grey zones of international law, namely the Russian involvement in the conflict in Ukraine, the legal classification of Russian actions, the right to self-determination and passportisation.